PREFERENSI OLAHAN UBI JALAR UNGU DAN UBIKAYU DI KABUPATEN MADIUN PROVINSI JAWA TIMUR - Aniswatul Khamidah (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2016)
ABSTRACTPreference of Processed Purple Sweet Potato and Cassava in Madiun District. ThroughSustainable Reserved Food Garden Model (SRFGM), women farmers group "Karya Mulya" was introduced to the technology of purple sweet potato and cassava processing, which have not been utilized optimally. This assessment aimed to determine the farmers’ acceptance of the introduced technologies, to know the most preferred product alongwith chemical and sensory quality and to know the ranking of product preferences with the influencing factors. This assessment was carried out in the Wonorejo village and Assessment Institute of Agricultural Technology (AIAT) East Java, using a randomized block design with 28 replicates. The treatments tested were purple sweet potato flour, purplesweet potato ice cream, purple sweet potato jams, purple sweet potato french fries, modified cassava flour, noodles, stick and brownies from modified cassava flour. Parameters observed were women farmer acceptance and preference of the processed technologies that have been introduced, the ranking of product preferences with the factors that influence and the nutrient composition. The assessment resulted that the farmers’ responses especially on the "easiness of processing" was 3.67-4.90; "easiness of obtaining raw materials" was from 3.38 to 4.95 (easy to very easy). The consumer preference value of the purple sweet potato products was on the range of 3.81 to 4.57 (like to very like). The rank of most preferred products were ice cream, french fries, jam and flour respectively. Ice cream had the highest preference containing of 64.93%; ash 2.15%; fat 2.20%; protein 2.94%; carbohydrate 27.78%; calories 142.70 cal/100 g and anthocyanins 0.23 mg/g. The panelist preference value of cassava products was between 4.05 and 4.524 (like to very like). For cassava product, the rank of the most favored products were brownies, noodles, stick and mocaf.Brownies encompassed the highest value with the water content of 30.11%; ash 1.78%; protein 5.88%; fat 19.20%;carbohydrates 43.02% and calories 368.43 cal/100 g. Factors that affecting adoption of technology are the simplicity of raw material (50%), easiness of process (44.44%), efficiency of labor (5.556%) and the simplicity of tool.Keywords: purple sweet potatoes, cassava, organoleptic testABSTRAKMelalui Kegiatan Model Kawasan Rumah Pangan Lestari (M-KRPL), kelompok wanita tani (KWT) “Karya Mulya” diperkenalkan teknologi olahan ubikayu dan ubi jalar ungu, yang selama ini pemanfaatannya belum optimal.Pengkajian bertujuan mengetahui penerimaan wanita tani terhadap teknologi yang diintroduksikan, mengetahui produk yang paling disukai beserta mutu kimia dan ensorisnya, serta mengetahui peringkat kesukaan produk dan faktor yang mempengaruhinya. Kegiatan dilaksanakan di Desa Wonorejo Kabupaten Madiun dan BPTP Jawa Timur, menggunakan Rancangan Acak Kelompok (RAK), 28 kali ulangan. Perlakuan yang diujikan yaitu tepung ubi jalar ungu, es krim ubi jalar ungu, selai ubi jalar ungu, french fries ubijalar ungu, tepung ubikayu termodifikasi, mie, stick dan brownies dari tepung ubikayu termodifikasi. Parameter yang diamati yaitu penerimaan dan preferensi wanita tani terhadap teknologi yang diintroduksikan, peringkat kesukaan produk dan faktor yang mempengaruhinya, sertakomposisi nutrisi produk terpilih. Hasil pengkajian menunjukkan bahwa penilaian petani mengenai teknologi yang diintroduksikan terutama “kemudahan cara pengolahan”, “kemudahan memperoleh bahan baku” berturut-turut sebesar 3,67-4,90; dan 3,38-4,95 (mudah sampai sangat mudah). Tingkat kesukaan konsumen pada olahan ubi jalar ungusebesar 3,81-4,57 (suka sampai sangat suka). Urutan olahan ubi jalar ungu dari yang paling disukai yaitu es krim, french fries, selai, dan tepung ubi jalar ungu. Es krim menempati nilai kesukaan tertinggi, dengan nilai kadar air 64,93%; abu 2,15%; lemak 2,20%; protein 2,94%; karbohidrat 27,78%; kalori 142,70 kal/100 gr; dan antosianin 0,23mg/g. Tingkat kesukaan panelis terhadap olahan ubikayu sebesar 4,05 sampai 4,524 (suka sampai sangat suka).Peringkat kesukaan olahan ubikayu dari yang paling disukai yaitu brownies, mie, stick dan tepung ubikayu termodifikasi. Brownies menempati nilai kesukaan tertinggi dengan nilai kadar air 30,11%; abu 1,78%; protein 5,88%; lemak 19,20%; karbohidrat 43,02% dan kalori 368,43 kal/100 gr. Faktor yang mempengaruhi adopsi teknologi yaitu kesederhanaan bahan (50%), kemudahan proses (44,44%), efisiensi tenaga kerja (5,556%) dan kesederhanaan alat.Kata kunci: ubijalar ungu, ubikayu, uji organoleptik